Medical Student Performance in Diagnosing Common Findings of CT Scan (Majalah Kedokteran Bandung, 2024)
Diagnostic radiology is a key diagnostic tool in many different conditions and ccrucial for monitoring, treating, and predicting outcomes. Accurately interpreting basic radiological images is a paramount skill for medical professionals. Therefore, this study aimed to assess clinical-phase medical students and interns' knowledge on evident findings on CT scans. This observational cross-sectional study was conducted in a single region in Saudi Arabia from May 2022 to December 2022. An electronic questionnaire were used to collect data. Twenty-one radiograph-based questions were used, for which students were asked to provide the best diagnosis and report their confidence for each question. Ethical approval was obtained. A convenience sampling technique was used to recruit the participants and SPSS were used for data analysis. Two hundred fifty-two medical students were included, with a mean age of 23.02 (SD=1.52) year. Of those, females comprised 65.1% and 86.1% of the total participants were in the clinical year. Most students with above-average knowledge were internship students (37.1%) compared to 9.7% among clinical year students (p=0.001). In addition, students with average knowledge had a higher level of confidence (7.62/10) compared with students with average knowledge (5.24) and students with below-average knowledge (5.24 and 5.057, respectively; p=0.001). In conclusion, the high percentage of incorrect responses reported by the current study reflects a strong deficit in the baseline CT knowledge among medical students. Further interventions are necessary to ensure better radiographic education for future physicians.
Keywords: Clinical Education; CT; diagnostic tools; medical students’ assessment